Utilization of Rambutan (Naphelium lappaceum L) Peel’s Waste is Becoming More Useful As a Natural Dye of Fabrics - Heny Kusumayanti; Vita Paramita; Rizka Amalia; Wahyuningsih Wahyuningsih (Diponegoro University, 2020)
The demand to find an alternatives source of fabric dyes is increasing nowadays, specifically for natural dye. Applying natural dye in fabric, giving important effect of more environmentally friendly than synthetic dye. One of the natural colors that can be used is Naphelium lappaceum L peel’s waste. The method used is dyeing a cloth with extract of Naphelium lappaceum L peels. Variables applied are extract concentration, type of fixation and concentration of fixation. The results of dyeing cotton fabric using Naphelium lappaceum L peel extract show that the use of alum solution as fixation materials provides brown light color, yellowish brown for lime, and blackish grey for ferro sulphate. The different extract concentration resulted significant effect on the colour radiance on fabric.